STRENGTH RESEARCH AND OPTIMIZATION DESIGN OF TWIST BEAM BASED ON FINITE ELEMENT ANALYSIS - TIAN Wei (Jixie qiangdu)
This article is focus on the crack problem of bench test in the development of twist beam,FEA and stress data collection are applied to comprehensive comparison,seek for the reason of crack,improved project is introduced with the manufacturing technique. CAE and sample bench test are applied to verify the feasibility of the project,the crack problem of bench test was solved by repeated optimization finally.（ In Chinese）